Graphitic microstructure and performance of carbon fibre Li-ion structural battery electrodes. Issue 1 (28th August 2018) - Fredi, Giulia; Jeschke, Steffen; Boulaoued, Athmane; Wallenstein, Joachim; Rashidi, Masoud; Liu, Fang; Harnden, Ross; Zenkert, Dan; Hagberg, Johan; Lindbergh, Göran; Johansson, Patrik; Stievano, Lorenzo; et al.
Abstract: Carbon fibres (CFs), originally made for use in structural composites, have also been demonstrated as high capacity Li-ion battery negative electrodes. Consequently, CFs can be used as structural electrodes; simultaneously carrying mechanical load and storing electrical energy in multifunctional structural batteries. To date, all CF microstructural designs have been generated to realise a targeted mechanical property, e.g. high strength or stiffness, based on a profound understanding of the relationship between the graphitic microstructure and the mechanical performance. Here we further advance this understanding by linking CF microstructure to the lithium insertion mechanism and the resulting electrochemical capacity. Different PAN-based CFs ranging from intermediate- to high-modulus types with distinct differences in microstructure are characterised in detail by SEM and HR-TEM and electrochemical methods. Furthermore, the mechanism of Li-ion intercalation during charge/discharge is studied by in situ confocal Raman spectroscopy on individual CFs. Raman G band analysis reveals a Li-ion intercalation mechanism in the high-modulus fibre reminiscent of that in crystalline graphite. Also, the combination of a relatively low capacity of the high-modulus CFs (ca. 150 mAh g −1 ) is shown to be due to that the formation of a staged structure is frustrated by an obstructive turbostratic disorder. In contrast, intermediate-modulus CFs, which have significantly higher capacities (ca. 300 mAh g −1 ), have Raman spectra indicating a Li-ion insertion mechanism closer to that of partly disordered carbons. Based on these findings, CFs with improved multifunctional performance can be realised by tailoring the graphitic order and crystallite sizes.